Large-scale screening of HBV epitopes restricted by multiple prevalent HLA-B/C allotypes and routine detection of HBV-specific T cells in CHB patients - Wu, Yandan; Zhao, Yu; Ji, Ruixue; Li, Pinqing; Chen, Huijuan; Yue, Fangping; Wu, Yi; Qiu, Jie; Shen, Chuanlai (Frontiers in Immunology, 2026)
Background and aimsIn our previous work, a total of 103 CD8+ T-cell epitopes restricted by 13 prevalent HLA-A allotypes in Northeast Asians were validated from the main proteins of hepatitis B virus (HBV). This study aims to further screen the T-cell epitopes restricted by 15 prevalent HLA-B and 14 prevalent HLA-C allotypes and establish a universal assay for counting reactive HBV-specific T cells in patients with chronic hepatitis B (CHB).MethodsCD8+ T-cell epitopes were systematically screened through a combination of in silico prediction, ex vivo co-cultures of peptides with patient-derived peripheral blood mononuclear cells (PBMCs), and peptide competitive binding assays using HLA-B/C transfected cell lines.ResultsA total of 89 novel CD8+ T-cell epitopes were identified from four HBV main proteins using PBMCs from 250 CHB patients. Furthermore, 201 validated CD8+ T-cell epitope peptides restricted by the 13 HLA-A, 15 HLA-B, and 14 HLA-C allotypes were integrated to construct a broad-spectrum epitope peptide library, and by which the ELISpot assay was established followed by clinical testing for 81 CHB patients. The counts of reactive HBV-specific T cells and T cells reactive to each HBV protein (HBsAg-, HBpol-, HBx-, or HBeAg-) in PBMCs showed a negative correlation with serum HBsAg levels and no correlation with HBeAg or ALT levels. NUCs/IFN-α combination elicited significantly more reactive HBV-specific T cells (including those targeting HBsAg, HBpol, HBx, or HBeAg) than NUCs or IFN-α monotherapy.ConclusionsThe proposed method holds great potential for facilitating routine evaluation of HBV-specific CD8+ T cell reactivity in CHB patients.